Employee’s Health Problems and Conditions at the Information Communication Industrial Sectors - et. al., R.Parvatharajan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Work-related physical factors include provisions for computerized workstations, length of employment (years of work at present, daily hours of the work as well as the hours of work per week, days per week, etc.);Physical workload (repetitive motion, forceful exertion, awkward positions, rapid hand & wrist movements, and forces related to the body structures); supply of work-breaks during work timings and environmental conditions such as lightening, noise, lack of clean air (Humidity), and frequent changes of indoor temperature etc. Information technology (IT) tasks have associated with the repetitive stress levels as well as with the problems related to the excessive exposure to the video display devices. Routine work, poorly designed tools such as computers and furniture in the Information and Communication Technology (ICT) work environment have dramatically increased work-related disorders (Blatter &Bongers, 2002) such as muscular skeletal issues.